Kosovo : Poverty Assessment, Promoting Opportunity, Security, and Participation for All - World Bank (Washington, DC, 2012)
Despite considerable progress with reconstruction in Kosovo, the challenge of poverty reduction remains enormous for years to come. The recent growth performance has been driven by a post-conflict boom financed by official development aid flows, but has not led to significant job creation opportunities, and its sustainability is unlikely without a clarification of Kosovo's political status, and the maintenance of peace and security. While recent growth (and consumption inequality) have most likely led to a reduction in poverty (between 2000 and 2003), yet, some 37 percent of the population is estimated to live in poverty according to the 2002/03 Household Budget Survey (HBS) data. The report seeks to contribute to the on-going policy dialogue on poverty reduction in Kosovo, and to support the formulation of public policy. The report outlines the many dimensions of poverty in Kosovo, where income poverty appears widespread, and is found to affect disproportionately children, the elderly, female headed households, the disabled, non-Serb ethnic minorities, the unemployed, and precarious job holders. Unemployment is in direct correlation with income poverty, but, while educational and health outcomes are still low, social cohesion is fragile, which may undermine the sustainability of economic growth, and reduce the impact of growth on poverty reduction. This strategy is articulated around the following five main goals: 1) promoting income opportunities; 2) raising education and health capabilities; 3) reducing vulnerability to income and non-income poverty; 4) empowering disadvantaged groups; and, 5) promoting a poverty dialogue. However, this strategy would need to take into account the context of tight fiscal constraints, in which public programs need to be developed. Moreover, to maximize the impact on poverty reduction, the links between growth and job creation need to be enhanced. This would require improved investment climate, and trade arrangements, in addition to advisory services provision to small farmers, in light of the intense competition they are facing due to subsidized agricultural imports.